ANALISIS PENGARUH KOMITMEN ORGANISAS! DAN KETERLIBATAN KERJA TERHADAP HUBUNGAN ANTARA ETIKA KERJA ISLAM DENGAN SIKAP PERUBAHAN ORGANISASI - Sri Anik; Arifuddin Arifuddin (Universitas Islam Nahdlatul Ulama Jepara, 2010)
Abstract This study examines the effect of Organizational Commitment and Job Involvement on the relationship between The Islamic Work Ethics and Organizational Change Attitude. The result of the study supports the hypothese that the Islamic Work EtNc relates to the Organizational Commitment and the Islamic Work Ethic related to the Organizational Change Attitude. In addition Job Involvement and the Organizational Commitment mediated the relationship between the lslamic Work Ethics and the Organizational Change Attitude whereas the result doesnt support the previous studies. The insignificant result was caused the Islamic Work Ethics universality which consists of honesty, merits, truth, shameful, self holiness, affection, simplicity and thrifty